The Informal Socio-Political Role Of Customary Institutions And Daily Socio-Political Dynamics In Kerinci Regency, Jambi Province: Peran Sosial Politik Informal Adat Dan Dinamika Sosial Politik Harian Di Kabupaten Kerinci Provinsi Jambi - Arif Roy Neldi (Jurnal Pemerintahan dan Politik, 2026)
Purpose: This study aims to analyze the informal socio-political role of Kerinci customary institutions in shaping the dynamics of everyday socio-political life in Kerinci Regency, Jambi Province. Methodology: This study employed a qualitative descriptive approach. Data were collected through semi-structured interviews with 17 informants and supported by document analysis. The data were analyzed using Homi K. Bhabha's, Hybridity Theory and Helmke and Levitsky's, Informal Institutions Theory through data reduction, data display, and conclusion drawing. The validity of the findings was ensured through triangulation. Findings: The findings reveal that customary institutions continue to function as informal socio-political institutions with strong legitimacy in conflict resolution, customary land governance, community aspiration channels, and the strengthening of social cohesion and local political stability. The interaction between customary institutions and formal government has produced a model of hybrid governance that enhances the effectiveness of local governance while preserving customary values. Practical Implication: Practically, this study recommends strengthening local government policies that integrate customary institutions as strategic partners in the governance of customary land, social conflict resolution, restorative justice–based criminal mediation, the preservation of customary values through tunjuk ajar (customary guidance), and the enhancement of community participation to support effective local governance grounded in local wisdom. Originality/value: This study proposes the concept of Kerinci Customary Democracy Hybridity, which explains that the relationship between customary institutions and electoral democracy operates in a complementary manner through the negotiation between customary legitimacy and state legitimacy.